2020
DOI: 10.1101/2020.04.03.022939
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Triphosphates of the Two Components in DESCOVY and TRUVADA are Inhibitors of the SARS-CoV-2 Polymerase

Abstract: SARS-CoV-2, a member of the coronavirus family, is responsible for the current COVID-19 pandemic. We previously demonstrated that four nucleotide analogues (specifically, the active triphosphate forms of Sofosbuvir, Alovudine, AZT and Tenofovir alafenamide) inhibit the SARS-CoV-2 RNA-dependent RNA polymerase (RdRp). Tenofovir and emtricitabine are the two components in DESCOVY and TRUVADA, the two FDA-approved medications for use as pre-exposure prophylaxis (PrEP) to prevent HIV infection. This is a preventati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…Remdesivir is the first agent to show preliminary clinical efficacy in an NIH randomized, placebo-controlled study (Wang et al, 2020) and the FDA has approved its Emergency Use Authorization for hospitalized patients with severe COVID-19. Tenofovir and emtricitabine can inhibit the RdRp of SARS-CoV-2 in vitro (Jockusch et al, 2020), and expected from our in silico analyses.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Remdesivir is the first agent to show preliminary clinical efficacy in an NIH randomized, placebo-controlled study (Wang et al, 2020) and the FDA has approved its Emergency Use Authorization for hospitalized patients with severe COVID-19. Tenofovir and emtricitabine can inhibit the RdRp of SARS-CoV-2 in vitro (Jockusch et al, 2020), and expected from our in silico analyses.…”
Section: Discussionsupporting
confidence: 68%
“…It is to be expected that NNRTIs as a class did not bind well to the catalytic site for the SARS-CoV-2 RdRp, which is the nucleoside/nucleotide triphosphate (NTP) binding site, where elongation of the RNA strand occurs (Gao et al, 2020). When NRTIs are metabolized and form triphosphate structures, they are capable of being added to the growing RNA/DNA strand and chain termination will follow (Gordon et al, 2020;Jockusch et al, 2020;Wang et al, 2020). However, HIV reverse transcriptase is inhibited by NNRTIs at a site different from that which the NRTIs bind to.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If Car-TP, Gan-TP or Ent-TP is incorporated and acts as a terminator, extension will stop; otherwise additional incorporation events may be observed. Guided by polymerase extension results we obtained previously for the active triphosphate forms of Sofosbuvir, Alovudine, AZT, Tenofovir-DP and Emtricitabine-TP (Ju et al 2020;Chien et al 2020;Jockusch et al 2020), various ratios of the nucleotides were chosen in the current work.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that five nucleotide analogues inhibit the SARS-CoV-2 RNA-dependent RNA polymerase (RdRp), including the active triphosphate forms of Sofosbuvir, Alovudine, Zidovudine, Tenofovir alafenamide and Emtricitabine (Ju et al 2020;Chien et al 2020;Jockusch et al 2020). Emtricitabine and Tenofovir alafenamide are used in FDA approved combination regimens for treatment of HIV/AIDS and hepatitis B virus (HBV) infections as well as pre-exposure prophylaxis (PrEP) to prevent HIV infections (Anderson et al 2011), and may be evaluated for PrEP for COVID-19 (Jockusch et al 2020).…”
Section: Selection Of Candidate Nucleoside Triphosphates For Coronavimentioning
confidence: 99%